2016
DOI: 10.5385/nm.2016.23.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings According to Feeding Diets in Very Low Birth Weight Infants: Human Breast Milk versus Bovine Milk-Based Formula

Abstract: Purpose: We aimed to compare the clinical findings, including morbidity, duration of parenteral nutrition, and length of hospital stay between very low birth weight infants (VLBWIs) fed bovine milk-based formula (BOV) and VLBWIs fed human breast milk (HBM) in a neonatal intensive care unit (NICU). Methods: VLBWIs admitted to the NICU of Dongsan Medical Center, Keimyung University, were enrolled. Infants born from March to August 2014 (n=28) were fed BOV (the BOV group), and those born from September to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…When these 3 studies were pooled, meta-analysis showed a significant protective effect of DHM on BPD36 (RR 0.80, 95% CI 0.68 to 0.95, p = 0.009). This protective effect of DHM on BPD36 was also observed when the 5 studies [20,32,35,36,38] that did not use DHM-based fortifier were pooled (RR 0.71, 95% CI 0.53 to 0.95, p = 0.022) and when the 8 studies were combined in a mixed-effects meta-analysis (RR 0.78, 95% CI 0.67 to 0.89, p = 0.0005, Figure 2). The study of Ginovart et al [32] also reported data on BPD28, and found no significant difference in this outcome between the group receiving DHM and the group receiving PF (RR 1.18, 95% CI 0.68 to 2.05, p = 0.560).…”
Section: Observational Studies: Donor Human Milk Vs Preterm Formulamentioning
confidence: 59%
See 4 more Smart Citations
“…When these 3 studies were pooled, meta-analysis showed a significant protective effect of DHM on BPD36 (RR 0.80, 95% CI 0.68 to 0.95, p = 0.009). This protective effect of DHM on BPD36 was also observed when the 5 studies [20,32,35,36,38] that did not use DHM-based fortifier were pooled (RR 0.71, 95% CI 0.53 to 0.95, p = 0.022) and when the 8 studies were combined in a mixed-effects meta-analysis (RR 0.78, 95% CI 0.67 to 0.89, p = 0.0005, Figure 2). The study of Ginovart et al [32] also reported data on BPD28, and found no significant difference in this outcome between the group receiving DHM and the group receiving PF (RR 1.18, 95% CI 0.68 to 2.05, p = 0.560).…”
Section: Observational Studies: Donor Human Milk Vs Preterm Formulamentioning
confidence: 59%
“…Based on the titles and abstracts of 1081 citations, we identified 139 potentially relevant studies ( Figure 1), 18 of which met the inclusion criteria [9,20,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The main characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations